KAJIAN PENGELOLAAN SAMPAH MEDIS DI RUMAH SAKIT X CILEGON - Edwina Leonita Pyopyash; Nurjazuli Nurjazuli; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2019)
Abstract:  Laundry Hospitals are health care facilities that are not only useful for the community, but can also be one of the causes of environmental pollution and health problems if poor waste management is carried out. Waste management in Hospital X is not optimal because the garbages are piled up and flies are seen in temporary dumps. The purpose of this research was to explains medical waste management is in Hospital X. The research tpe used was observational with a cross sectional approach. Population is policy makers and waste management officers. The samples taken were 2, namely 1 sanitarian and 1 person in charge of medical waste. The results of research from X Cilegon Hospital showed that medical waste produced was 106.79 kg/day. Based on the results of the assessment in the aspect of waste management, most of them still experience deficiencies because the process steps carried out are not in accordance with the standards set. Based on the Minister of Health Regulation number 7 of 2019 concerning Hospital Environmental Health the results of medical waste management has met the requirements because it has a value of 80% of the total score is 100%. In addition, problems that occur such as every day there is still unmanaged waste and the medical waste officer do not use personal protective equipment completely..